Efficient syntheses of alpha- and beta-C-nucleosides and the origin of anomeric selectivity12. Issue 12 (16th May 2018) - Liu, Tongchao; Zhu, Zhengdan; Ren, Huanming; Chen, Yabin; Chen, Guohua; Cheng, Maosheng; Zhao, Dongmei; Shen, Jingkang; Zhu, Weiliang; Xiong, Bing; Chen, Yue-Lei
Abstract : Valuable C -nucleosides are efficiently prepared with excellent anomeric selectivity depending on protecting groups on sugar moiety. Abstract : C -Nucleosides constitute a valuable class of compounds in biological and medicinal chemistry studies. We report herein a new and efficient synthesis of both alpha - and beta-C -nucleosides with high anomeric selectivity from N 6 -Boc protected purine analogues. The synthetic approach features a carefully designed lithiation and silane reduction sequence. The anomeric stereochemistry outcome is dictated by the protecting group of sugar lactones. Computational studies suggest that previously neglected interactions between partially positively-charged silane and the substitutions on a sugar moiety play important roles in the anomeric selectivity of silane-mediated C -nucleoside synthesis.